The Influence Of Competence And Discipline On Motivation And Its Impact On The Performance Of Teachers Of The Musi Banyuasin Islamic Boarding School - Faizal Faizal; Diah Isnaini; Trisniarty A M (Jurnal Sosial Teknologi, 2022)
This study aims to determine the influence of competence and discipline on motivation and its impact on the performance of Islamic Boarding School teachers in Sungai Lilin District, Musi Banyuasin Regency. This type of research is Associative. The variables used are competence, discipline, motivation, and performance, which are developed into 12 indicators. The sample in this study was teachers of Islamic Boarding Schools in Sungai Lilin District, Musi Banyuasin Regency, totaling 120 people selected by cluster sampling. The data used are primary data with the method of collecting questionnaire data. Structural Equation Modeling (SEM) with the Lisrel program is the analysis technique. The results of this study prove that: 1) competence has a positive and significant effect on the motivation of Pondok Pesantren teachers, 2) discipline has a significant effect on the motivation of Pondok Pesantren teachers, 3) competence has a positive and insignificant effect on the performance of Pondok Pesantren teachers, 4) discipline has a negative and insignificant effect on the performance of Islamic Boarding School teachers, 5) motivation has a positive and significant effect on the performance of Pondok Pesantren teachers in sub-districts. Lilin River, Musi Banyuasin Regency. Based on the discussion results, it is proven that motivation can strengthen the influence of competence and discipline on performance.